Politization, participation, and innovation: Socializing agricultural research in Bolivia - Córdoba, Diana (2017)
Using the case of agricultural research in Bolivia during the neoliberal period, this paper argues that there is a need to bring politics into science, but differentiates between two levels: politics as a mode of governance or a political project that shapes the scientific process (macro-politics), and politics as an eternal process of contestation in society (micro-politics). To support this argument, we focus on the Foundation for the Promotion and Research of Andean Products (PROINPA) to demonstrate how the “macro-political” project of neoliberalism decentralized and privatized agricultural research services, redefining research agendas, and the relationship between researchers and end-users of technology; and, in turn, how researchers responded to this project, adapting and contesting neoliberalism in their everyday activities (micro-politics).